The Cultural Legacy of Victorino Abente y Lago (1846-1935) in Paraguay: “The First Interpreter of National Sentiment” - Duncan Webb, Philip (Madrygal. Revista de Estudios Gallegos, 2020)
First cousin to Pondal, uncle and father-in-law to Gonzalo López Abente – the importance of the poet and journalist Victorino Abente y Lago (1846-1935) is equal to that of his most well-known relatives. Juan O’Leary, the great theorist of Paraguayan nationalism, in an article in 1923 described Abente y Lago as the “patriarch of our poetry” and “the first interpreter of nacional sentiment”. This contribution aims to recover the memory of a person –for various reasons forgotten both in Paraguay and in his native Galicia– who played a fundamental part in Paraguayan literary development in the late nineteenth and early twentieth centuries, as well as in the very construction of Paraguayan nationality. In this sense, the works of Abente y Lago can be defined as a tangible though unrecognised projection of Galician culture far beyond its borders. This analysis is organised into three sections. Firstly we examine the secondary literature underlying this study, the basic outline of the poet’s life and the Paraguayan historical context, and secondly the contents and meanings of his most famous composition, La Sibila paraguaya (1886), as well as how it was received by his contemporaries. Finally, in the third section we summarise the later influence of this poem upon Paraguayan literature and thought at the beginning of the twentieth century.
Keywords: Emigration; Literature; Poetry; Nationalism; Paraguay; Victorino Abente y Lago